Five new species of Chromagallia from South America (Insecta: Hemiptera: Cicadellidae: Agalliinae) - Gonçalves, Ana Clara; Mejdalani, Gabriel; Costa, Luiz Alves (Zootaxa, 2008)
Five new species of Chromagallia Linnavuori, 1954, C. lamasi sp. nov., C. carvalhoi sp. nov., C. zanolae sp. nov., C. lanceolata sp. nov. (all from Brazil) and C. paraguayensis sp. nov. (Paraguay, new country record), are described and illustrated. These species can be distinguished mainly by the aedeagal and pygofer morphology. Agallia longistilata Coelho & Dutra, 1992 is transferred to Chromagallia and newly recorded from Paraná State, southern Brazil. By the addition of these taxa, the number of Chromagallia species is increased to eight, with seven of them occurring in Brazil. The female genitalia in Chromagallia are described and illustrated in detail for the first time. A key to the species and taxonomic notes on the genus are provided.